Soluble CD30 serum concentrations inversely correlate with hand bone mineral density in patients with active rheumatoid arthritis under the treatment of low-dose methotrexate - Ozgocmen, S; Ardicoglu, O; Kamanli, A; Godekmerdan, A; Hacievliyagil, C (Elsevier Science Inc, 2003)
[Abstract Not Available]
1ST Joint meeting of the International-Bone-and-Mineral-Society/Japanese-Society-for-Bone-and-Mineral-Research -- JUN 03-07, 2003 -- OSAKA, JAPAN